T-antigen binding lectin with antibacterial activity from marine invertebrate, sea cucumber (Holothuria scabra): possible involvement in differential recognition of bacteria - Gowda, Nagaraj M.; Goswami, Usha; Khan, Mohammad Islam (Journal of Invertebrate Pathology, 2008)
In invertebrates, cellular and humoral components are evolved to maintain their body immunity and integrity. Both these factors respond to different antigens such as microorganisms, vertebrate erythrocytes and foreign proteins. In this article, we report a study of a lectin (HSL) involved in immune response in the echinoderm, sea Cucumber (Holothuria scabra). Correlative studies indicate that the expression of this defensive lectin is induced by bacterial challenge, wherein cell wall glycoconjugates of bacteria are involved in lectin induction. HSL showed strong broad spectrum antibacterial activity against both gram-positive and gram-negative bacteria. Under in vitro conditions, purified HSL mediate agglutination of the test bacteria, there by indicating a possible mode of action in physiological situation. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: agglutination; antibacterial activity; coelomic fluid; Holothuria scabra; Lectin; sea cucumber